Physical Therapists and Physicians Evaluate Nonarthritic Hip Disease Differently: Results From a National Survey. Issue 6 (4th March 2020) - Brown-Taylor, Lindsey; Lynch, Andrew; Foraker, Randi; Harris-Hayes, Marcie; Walrod, Bryant; Vasileff, W Kelton; Glaws, Kathryn; Di Stasi, Stephanie
Abstract: Background: Physical therapy and surgery are viable treatment options for nonarthritic hip disease (NAHD). Interdisciplinary collaboration can help patients make informed treatment decisions. Understanding how each provider can contribute is a critical first step in developing collaborative evaluation efforts. Objective: The objective of this study was to describe the current evaluation of NAHD by both physical therapists and physicians, and evaluate national use of expert-recommended evaluation guidelines. Design: A national survey study distributed in the United States was implemented to accomplish the objective. Methods: A survey was distributed to 25, 027 potential physical therapist and physician respondents. Respondents detailed their evaluation content for patients with NAHD across the following domains: patient-reported outcomes, patient history, special tests, movement assessment, clinical tests, and imaging. Respondents ranked importance of each domain using a 5-point Likert scale (not important, slightly important, important, very important, or extremely important). Odds ratios (ORs [95% CIs]) were calculated to identify the odds that physical therapists, compared with physicians, would report each evaluation domain as at least very important. Fisher exact tests were performed to identify statistically significant ORs. Results: Nine hundred and fourteen participants (3.6%) completed the survey. Physical therapists were more likely to indicate movement assessment (OR: 4.23 [2.99–6.02]) and patient-reported outcomes (OR: 2.56 [1.67–3.99]) as at least very important for determining a diagnosis and plan of care. Physical therapists had lower odds of rating imaging (OR: 0.09 [0.06–0.14]) and special tests (OR: 0.72 [0.53–0.98]) as at least very important compared with physicians. Limitations: This survey study did not include many orthopedic surgeons and thus, primarily represents evaluation practices of physical therapists and nonsurgical physicians. Conclusions: Physical therapists were more likely to consider movement assessment very important for the evaluation of patients with NAHD, whereas physicians were more likely to consider imaging and special testing very important.